PENGEMBANGAN MATERI DAN MODEL PENDIDIKAN KARAKTER BERBASIS BUDAYA PADA SISWA SMP - Ni Nyoman Lisna Handayani (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
Character building and national identity are noble ideals that must be realized throughthe provision of directed and sustainable education. Character is a character, character, character,or personality that is formed from the results of internalizing various virtues that are believedand used as a basis for perspective, thinking, acting, and acting. Virtue consists of a number ofvalues, morals, and norms, such as honesty, courage to act, trustworthiness, and respect forother people. Interaction with other rangers fosters community character and national character.Therefore, developing national character can only be done through the development of one'sindividual character. However, because humans live in a particular social and culturalenvironment, the development of individual character can only be carried out in the relevantsocial and cultural environment. That is, the development of culture and national character canonly be done in an educational process that does not release students from the social, cultural,and national culture. The social environment and national culture are Pancasila, so culturaleducation and national character must be based on Pancasila values. That is, educating theculture and character of the nation is developing Pancasila values in students through educationof the heart, nature, and physical.